RISET DAN ANALISIS MANAJEMEN ARSIP STATIS PADA WEBSITE NATIONAL ARCHIVES OF AUSTRALIA SECARA ONLINE - Hendra Junawan; Rezki Deritani (Maktabatuna, 2020)
This Atrikel describes the management of Static records in an institution which includes management of records, acquisition of records, schedule of retention of records and other information relating to a static archive and the ease of searching an archive through an online website that enables the ease of retrieval archive information. The method used in this study uses a qualitative type using a descriptive approach, and in the process of collecting data in the field of researchers themselves who become research instruments by collecting data from the observation process directly on the National Archives of Australia website. The results of this study indicate that the National Archives of Australia in its management is very good and its acquisition process also varies and in this case it can be seen that the National Archives of Australia has various types of collections such as paper files, have photos, audiovisual records and sound recordings so that in terms of this can make it easier for users to search information and retrieve static archive information.